Penguatan Etika Politik Pancasila bagi Pemilih Pemula melalui Observasi Tradisi Saparan di SMA Islam Plus At Tohari (Lembaga Pengembangan Kinerja Dosen, 2026)
Political education for first-time voters plays a crucial role in instilling democratic awareness rooted in Pancasila values. One method that can be implemented is through field observation assignments that utilize local wisdom. This study aims to examine how the Saparan tradition can be used as a learning medium in developing Pancasila political ethics for first-time voters at SMA Islam Plus At Tohari. The research approach used was qualitative, with data collection techniques including observation, interviews, and documentation. The results revealed that students' involvement in field observation assignments on the Saparan tradition helped them understand the values of democracy, mutual cooperation, and leadership from a local cultural perspective. The experience of direct interaction with the community also plays a role in shaping ethical political awareness in accordance with Pancasila principles. Therefore, integrating political education with local wisdom through field observation methods can be an effective approach in strengthening the understanding of political ethics for first-time voters.